Precision-Engineered Construction of Proton-Conducting Metal–Organic Frameworks - Zhu, Liyu; Yang, Hongbin; Xu, Ting; Shen, Feng; Si, Chuanling (Nano-Micro Letters, 2024)
Proton-conducting materials have attracted considerable interest because of their extensive application in energy storage and conversion devices. Among them, metal–organic frameworks (MOFs) present tremendous development potential and possibilities for constructing novel advanced proton conductors due to their special advantages in crystallinity, designability, and porosity. In particular, several special design strategies for the structure of MOFs have opened new doors for the advancement of MOF proton conductors, such as charged network construction, ligand functionalization, metal-center manipulation, defective engineering, guest molecule incorporation, and pore-space manipulation. With the implementation of these strategies, proton-conducting MOFs have developed significantly and profoundly within the last decade. Therefore, in this review, we critically discuss and analyze the fundamental principles, design strategies, and implementation methods targeted at improving the proton conductivity of MOFs through representative examples. Besides, the structural features, the proton conduction mechanism and the behavior of MOFs are discussed thoroughly and meticulously. Future endeavors are also proposed to address the challenges of proton-conducting MOFs in practical research. We sincerely expect that this review will bring guidance and inspiration for the design of proton-conducting MOFs and further motivate the research enthusiasm for novel proton-conducting materials. Highlights: 1 The effects of the size structure and stability of metal–organic frameworks (MOFs) on proton conduction are comprehensively summarized. 2 Advanced strategies for constructing proton conduction MOFs are critically discussed. 3 Challenges and opportunities for the development of novel proton-conducting MOFs are further outlined.